Anti‐inflammatory roles of p38α MAPK in macrophages are context dependent and require IL‐10. Issue 5 (1st November 2017) - Raza, Abbas; Crothers, Jessica W.; McGill, Mahalia M.; Mawe, Gary M.; Teuscher, Cory; Krementsov, Dimitry N.
Abstract : p38α MAP kinase signaling in macrophages plays context‐dependent pro‐ and anti‐inflammatory roles, with the latter dependent on IL‐10. Abstract : The p38 MAPK pathway was originally identified as a master regulator of proinflammatory cytokine production by myeloid cells. Numerous drugs targeting this kinase showed promise in preclinical models of inflammatory disease, but so far, none have shown efficacy in clinical trials. The reasons behind this are unclear, but may, in part, be explained by emerging anti‐inflammatory functions of this kinase or overly refined selectivity of second‐generation pharmacologic inhibitors. Here, we show that p38α signaling in macrophages plays pro‐ and anti‐inflammatory functions in vivo and in vitro, with the outcome depending on the stimulus, output, kinetics, or mode of kinase inhibition (genetic vs. pharmacologic). Different pharmacologic inhibitors of p38 exhibit opposing effects, with second‐generation inhibitors acting more specifically but inhibiting anti‐inflammatory functions. Functionally, we show that the anti‐inflammatory functions of p38α in macrophages are critically dependent on production of IL‐10. Accordingly, in the absence of IL‐10, inhibition of p38α signaling in macrophages is protective in a spontaneous model of colitis. Taken together, our results shed light on the limited clinical efficacy of drugs targeting p38 and suggest that their therapeutic efficacy can be significantly enhanced by simultaneous modulation of p38‐dependent anti‐inflammatory mediators, such as IL‐10.